Postoperative Outcome of Combined Phacovitrectomy in Eyes with Excessive Myopia (>-30 D) - Hua Fan; Mingming Zhang; Radouil Tzekov; Zhuyun Qian; Jiasong Yang; XiaoLin Xie; Wensheng Li (Case Reports in Ophthalmological Medicine)
Background. To report the outcomes of phacoemulsification combined with vitrectomy in eyes with extreme myopia (-30 diopters or more). Case Presentation. Three patients with cataract, vitreous opacities, and extreme myopia of more than -30 diopters underwent a combined surgical procedure of cataract extraction combined with vitrectomy. Postoperative refractive correction of the three cases ranged from -1.0 D to -2.5 D spherical equivalent. There was an obvious hyperopic shift of all cases. All patients noted a significant improvement in uncorrected and best-corrected visual acuity from 0.4 to 0.8 in case 1, from CF/70 cm to 1.0 in case 2, and from 0.12 to 0.5 in the right eye and 0.15 to 0.2 in the left eye in case 3. Vitreous floaters disappeared in all cases. No complications were noted during follow-up. Conclusions. To the best of the authors’ knowledge, these represent the first reported clinical cases of combined cataract extraction+vitrectomy surgery in eyes with extreme (>-30 D) myopia. Our results support the notion that phacoemulsification combined with vitrectomy may be a good therapeutic option for cataracts and vitreous floaters in cases with extreme myopia.